An assessment of recent thermal radiation model performance for propane gas fire experiments - Chong Vui San, Michael; Mohd Tohir, Mohd Zahirasri; Spearpoint, Michael; Saadon, Syamimi; Abu Talib, Abd. Rahim (SAGE Publications Ltd, 2024)
In this article, the performance of five radiation models is investigated, including one conventional radiation model, that is, single-point source model, as well as four recently developed models, that is, a weighted multipoint source model, a cuboid flame model, a multicuboid flame model and a multicylinder flame model. The models are assessed in terms of the height of a target above flame base, the horizontal distance of target from flame source, heat release rate and size of burner. The estimations of the theoretical models are compared with propane-based experimental data with heat release rate ranging from 100 to 300 kW and assessed through numerical and graphical analysis. From the results obtained, the single-point source model outperformed the recently developed radiation models in estimating radiant heat received by an object located at a distance from the fire source, albeit it does exhibit some sensitivity to modifications in input parameters.